Peculiarities of pulse plasma streams interaction with different materials surfaces - Zhukeshov, A.M. (Recent Contributions to Physics, 2012)
The methods of metallography and x-ray spectral analysis is studied surface of constructional materials of different density after exposure to pulsed plasma flow. is shown The spray uneven depending on the angle of reflection and leads to the formation of the surface film of various thickness and dust buffer plasma.